1995
DOI: 10.1002/ar.1092410404
|View full text |Cite
|
Sign up to set email alerts
|

Spermatozoal ultrastructure in three species of parrots (Aves, psittaciformes) and its phylogenetic implications

Abstract: (1) These features are tetrapod symplesiomorphies, (2) is an amniote synapomorphy; the fibers differ from those of reptiles in being uniform in size, (3) loss of the fibrous sheath is an apomorphy known elsewhere only in columbiforms, (4) are apomorphies relative to basal aminiotes (Chelonia, Sphenodon, and Crocodilia), (5) is an apomorphic condition shared with other nonpasserines (galliforms and the white-naped crane) and crocodilians, (6) the latter taxa differ from parrots in a plesiomorphic elongation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 32 publications
(59 reference statements)
5
26
0
Order By: Relevance
“…In common with other ratites the nuclear rostrum in emu sperm extends deep within the acrosome, resulting in the lateral profiles of the acrosome thinning towards the acrosome-nuclear shoulder. The acrosome of the budgerigar, parrots and cockatiel, although also conical in form, does not form a cap over the tip of the nucleus as described in ratites, but ends adjacent to the nucleus without overlapping it [19][20][21]. Not all non-passerines have a cap-like acrosome, for example, in the white-naped crane [22], jacana [23] and woodpecker [24], a small spherical, button-like acrosome has been described which nestles at the blunt apex of the nucleus.…”
Section: Transmission Electron Microscopymentioning
confidence: 98%
See 1 more Smart Citation
“…In common with other ratites the nuclear rostrum in emu sperm extends deep within the acrosome, resulting in the lateral profiles of the acrosome thinning towards the acrosome-nuclear shoulder. The acrosome of the budgerigar, parrots and cockatiel, although also conical in form, does not form a cap over the tip of the nucleus as described in ratites, but ends adjacent to the nucleus without overlapping it [19][20][21]. Not all non-passerines have a cap-like acrosome, for example, in the white-naped crane [22], jacana [23] and woodpecker [24], a small spherical, button-like acrosome has been described which nestles at the blunt apex of the nucleus.…”
Section: Transmission Electron Microscopymentioning
confidence: 98%
“…In some galliform birds, such as the chicken, it extends approximately halfway beneath the acrosome, whereas in the turkey [30], duck [31] and white-necked crane [22] the perforatorium is comparatively short and limited to the posterior aspect of the acrosome. In the budgerigar [19] and parrots [20], it is an extremely long structure, extending almost the full length of the sub-acrosomal region. The situation in palaeognaths is strikingly different.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…In addition, the rostrum in ratites bears an equally extensive endonuclear canal. It is noteworthy that the anterior tip of the nucleus of the Budgerigar, 28,135 white-naped Crane, 136 cockatiel (Fig. 10F, G), and peach-faced lovebird 45,135 does not project into the subacrosomal space, as in other birds, but makes a direct, en face contact with the caudal rim of the acrosome.…”
Section: -126mentioning
confidence: 99%
“…However, the concentration of intermediate filaments denoting this region as the acroplaxome in rodents (Kierszenbaum et al, 2003) is not observed. Whereas in mammals the acrosome covers the anterior two thirds of the nucleus, in non-passerine and sub-oscine birds it is short relative to the length of the nucleus (Jamieson et al, 1995). In ratites it covers approximately 10% of the nucleus and would therefore have little influence on head shaping in general except for the formation of the nuclear rostrum as described above.…”
Section: The Perinuclear Theca (Pt)mentioning
confidence: 99%
“…This would appear unlikely in non-passerines as a conical acrosome is formed in a number of species without the presence of a nuclear rostrum (Humphreys, 1975;Jamieson, 2007;Jamieson et al, 1995;Lovas et al, 2012;Phillips et al, 1987;Saita et al, 1982;Samour et al, 1986), although a well-developed perforatorium may fulfill this role. In these birds the acrosome ends adjacent to the nucleus and does not overlap it.…”
Section: Role Of the Forming Acrosomementioning
confidence: 99%